Analysis of Educational Inequality on Economic Growth in South Sumatra - Zalianti, Olvy Dica; Indraswanti, Bertha Esti Iin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze how big the educational inequality is and what factors influence it, such as poverty, population, government spending in the education sector, and per capita income, and how big its influence is on economic growth in the Province. This study is secondary data sourced from the Central Statistics Agency and the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia. The data analysis method used is the Education Gini Index and panel data regression analysis with the Fixed Effect Model. The regression analysis uses two models, the first model's independent variables are poverty, population, government spending in the education sector, and per capita income while the dependent variable is educational inequality. The second model's independent variable is educational inequality while the dependent variable is economic growth. The results of the study show that educational inequality in South Sumatra Province in 2023 is at a low inequality level of 0.27. The results of the analysis in the first regression model show that poverty has a significant positive effect on educational inequality, while educational spending and per capita income have a significant negative effect.While the second regression model shows that educational inequality has a significant negative effect on economic growth.